Study of Rural-Urban Fringe Patterns of Sargodha City, Pakistan - Nadeem, Muhammad; Mohsin, Muhammad; Rafique, Anum; Rehman, Abdur (International Journal of Economic and Environmental Geology, 2023)
Urban fringe is a transitional zone of various land uses between urban and rural lands with a low population density that is lower than urban centre but higher than the countryside. The current study focuses on the spatial and structural pattern of the rural-urban fringes of Sargodha city which is one of the rapidly growing cities in Pakistan. To analyze the spatial pattern of rural-urban fringe five study sites were identified such as Gulberg Town, 49 Tail, 85 Jhaal, Jhaal Chakian and Johar Colony different techniques were utilized. Primary and secondary collected data were used for field surveying besides the interview based on a designed and partially structured questionnaire. Maps were prepared with the help of the Geographic Information System (GIS) and remote sensing. Results revealed that many commercial centres were situated on the edges of the city. The structure and pattern of these localities were recognized and it is found that urban impacts have not only transformed the socio-economic and demographical shape of the rural-urban fringes but also the pattern of land use of the study area. It shows that GIS and remote sensing are essential techniques to map out the spatial changes at the urban fringe.